A meta-analysis of the association of G915C, G800A, C509T gene polymorphism of transforming growth factor-β1 with diabetic nephropathy risk. (March 2014) - Zhang, Jie; Guan, Ya-Li; Xiao, Yan; Zhang, Xian-Wen
Abstract This meta-analysis was conducted to evaluate the association of transforming growth factor-β1 (TGF-β1) G915C, G800A, C509T gene polymorphism with the risk of diabetic nephropathy (DN). The association literatures were identified from PubMed, Cochrane Library, and CBM-disc (China Biological Medicine Database) on March 1, 2013, and eligible reports were recruited and synthesized. Seven reports were recruited into this meta-analysis for the association of TGF-β1 G800A, C509T, G915C gene polymorphism with DN risk. GG genotype, CC genotype, and C allele of TGF-β1 G915C were not associated with the DN risk (GG: OR = 0.84, 95% CI: 0.62–1.14, p = 0.27; CC: OR = 1.05, 95% CI: 0.50–2.22, p = 0.90; C allele: OR = 1.16, 95% CI: 0.88–1.51, p = 0.29). Furthermore, TGF-β1 G800A, C509T gene polymorphism was not associated with the DN risk. In conclusion, TGF-β1 G915C, G800A, and C509T gene polymorphism are not associated with the DN risk. However, more studies should be performed to confirm this relationship in the future.